2021
DOI: 10.1097/cce.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Improvement in Respiratory Acidosis Using Extracorporeal Co 2 Removal With Hemolung Respiratory Assist System in the Management of Severe Respiratory Failure From Coronavirus Disease 2019

Abstract: Objectives: About 15% of hospitalized coronavirus disease 2019 patients require ICU admission, and most (80%) of these require invasive mechanical ventilation. Lung-protective ventilation in coronavirus disease 2019 acute respiratory failure may result in severe respiratory acidosis without significant hypoxemia. Low-flow extracorporeal C o 2 removal can facilitate lung-protective ventilation and avoid the adverse effects of severe respiratory acidosis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The study further supports the findings from several other previous studies that low-flow ECCO 2 R devices such as Hemolung are effective in improving hypercapnia while reducing the lung injury due to invasive mechanical ventilation (8,11,14,16,20). The overall survival rate of patients in this study is about 41% and is comparable with other studies that used ECCO 2 R (8,23,24). The mortality observed in this study showed significant differences across the diagnostic categories with a very low survival in COVID-19 ARDS patients (31%).…”
Section: Relationship With Previous Studiessupporting
confidence: 91%
“…The study further supports the findings from several other previous studies that low-flow ECCO 2 R devices such as Hemolung are effective in improving hypercapnia while reducing the lung injury due to invasive mechanical ventilation (8,11,14,16,20). The overall survival rate of patients in this study is about 41% and is comparable with other studies that used ECCO 2 R (8,23,24). The mortality observed in this study showed significant differences across the diagnostic categories with a very low survival in COVID-19 ARDS patients (31%).…”
Section: Relationship With Previous Studiessupporting
confidence: 91%
“…4 HRAS has also been reported to improve acidosis in acute respiratory failure from coronavirus disease 2019. 9 Rajab et al reported the use of VV-ECMO via a right internal jugular Avalon cannula as a bridge to heart and lung transplantation in a patient with dextrocardia. 10 In our patient this was not an option because her superior and inferior vena cava were on the left side and her tricuspid valve was facing the right.…”
Section: Discussionmentioning
confidence: 99%
“…Bonnin et al reported using HRAS for severe chronic obstructive pulmonary disease bridge to lung transplant; a transplant was performed 31 days after induction of HRAS 4 . HRAS has also been reported to improve acidosis in acute respiratory failure from coronavirus disease 2019 9 …”
Section: Discussionmentioning
confidence: 99%
“…When compared to patients with normal ABG readings, RANC and MAC doubled the risk of fatality. Lung-protective ventilation in COVID-19 respiratory failure may result in severe respiratory acidosis without considerable hypoxemia [34]. The higher mortality rate in patients with respiratory acidosis may be due to the binding of protein S to angiotensin-converting enzyme 2 receptors, which penetrate alveolar epithelial cells, resulting in direct toxic effects and an overactive immune response.…”
Section: Demographic Data Of the Enrolled Patientsmentioning
confidence: 99%